The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1021/es071607j
|View full text |Cite
|
Sign up to set email alerts
|

Bioturbation-Driven Release of Organic Contaminants from Baltic Sea Sediments Mediated by the Invading Polychaete Marenzelleria neglecta

Abstract: Baltic Sea sediments are among the world's most polluted regarding eutrophication and contamination. Eutrophication-induced hypoxia has caused depletion of bioturbating macrofauna in vast areas, producing laminated sediments. We investigated if reoxygenation and colonization by the invading deep-burrowing polychaete Marenzelleria neglecta may cause an augmented contaminant release from Baltic Sea sediments. Intact laminated sediment cores were exposed either to in situ hypoxia, reoxygenation, or reoxygenation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
54
3
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 48 publications
(66 reference statements)
8
54
3
4
Order By: Relevance
“…The bioturbation of sediments by large benthic invertebrates alters sediment redox chemistry by mixing pre-stratified zones in the sediment, and increasing the penetration of electron acceptors such as dissolved O 2 , NO 3 -and SO 4 2-into anoxic sediments (Aller et al, 2001;Granéli, 1979;Matisoff et al, 1985;Pischedda et al, 2008; Volkenborn et al, 2010). Redox changes can alter metal binding affinities between the solid and dissolved phases, significantly modifying the speciation and bioavailability of most metals in sediments (De Jonge et al, 2012;Doyle and Otte, 1997;Granberg et al, 2008). The concentration of AVS has a major influence on metal bioavailability, and for sediments containing a molar excess of acid volatile sulfide (AVS) over simultaneously extractable metals (SEM, ΣCd, Cu, Ni, Pb, Zn), it is predicted that the porewater concentrations of these metals will be negligible and should not cause direct toxicity to benthic organisms Hansen et al, 2005;Lawrence et al, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…The bioturbation of sediments by large benthic invertebrates alters sediment redox chemistry by mixing pre-stratified zones in the sediment, and increasing the penetration of electron acceptors such as dissolved O 2 , NO 3 -and SO 4 2-into anoxic sediments (Aller et al, 2001;Granéli, 1979;Matisoff et al, 1985;Pischedda et al, 2008; Volkenborn et al, 2010). Redox changes can alter metal binding affinities between the solid and dissolved phases, significantly modifying the speciation and bioavailability of most metals in sediments (De Jonge et al, 2012;Doyle and Otte, 1997;Granberg et al, 2008). The concentration of AVS has a major influence on metal bioavailability, and for sediments containing a molar excess of acid volatile sulfide (AVS) over simultaneously extractable metals (SEM, ΣCd, Cu, Ni, Pb, Zn), it is predicted that the porewater concentrations of these metals will be negligible and should not cause direct toxicity to benthic organisms Hansen et al, 2005;Lawrence et al, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…To obtain sufficient detection sensitivity, the cross-section area of a sorbent phase must be large enough to induce large amounts of chemicals to be released from sediment. In addition, although the benthic chamber approach has not been found to influence ebullition-facilitated flux [47], the vitality of benthic organisms inside the chamber may decrease after a few days under anaerobic conditions, thereby leading to a reduction in the bioturbation-driven release of chemicals [48]. …”
Section: Main Drawbacksmentioning
confidence: 99%
“…The great capacity of Marenzelleria-bioturbated sediments to store phosphorus was demonstrated by the fact that twice as much was bound annually to the present-day oxic sediments in the Stockholm archipelago as annually could be removed by the sewage treatment plants in Stockholm. Another possibility is that changed redox conditions in the sediment and activity of Marenzelleria spp. could increase the flux of contaminants such as PCBs compared to if the sediment remains anoxic (Granberg et al, 2008). showed that contaminants and cadmium could be either buried or remobilized in the sediment because of the activity of different infaunal species.…”
Section: Bioturbation and Related Benthic Biogeochemical Processesmentioning
confidence: 99%